The evolution of Neolithic and Bronze Age landscapes : from Danubian longhouses to the stone rows of Dartmoor and Northern Scotland - Carnes, Alexander, (Archaeopress archaeology., 2014)
At the heart of this book is a comparative study of the stone rows of Dartmoor and northern Scotland, a rare, putatively Bronze Age megalithic typology that has mystified archaeologists for over a century. It is argued that these are 'symbols' of Neolithic long mounds, a circumstance that accounts for the interregional similarities; other aspects of their semantic structures are also analysed using rigorous semiotic theory. The research presented here takes an evolutionary approach, drawing on biological theory to explain the active role of these monuments in social evolution and to investigate the processes at work in the development of prehistoric landscapes.